PENGARUH LAYANAN KONSELING KELOMPOK TEKNIK ROLE PLAYING TERHADAP KECEMASAN BERBICARA DI DEPAN KELAS PADA SISWA KELAS X SMA YAYASAN PERGURUAN KARYA PEMBANGUNAN DELI TUA - Sri Anisa; Nurul Azmi Saragih; Dina Hidayati Hutasuhut; Vinda Chairunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Public speaking anxiety is characterized by feelings of fear, nervousness, and distress when addressing an audience. This study aims to determine the effect of group counseling services utilizing role-playing techniques on classroom speaking anxiety among Grade X students at SMA Yayasan Perguruan Karya Pembangunan Deli Tua. Group counseling employing a role-playing approach plays a crucial role in reducing students' speaking anxiety. Through the application of this technique, students are expected to overcome various obstacles—such as difficulties in building relationships, empathizing with others, and a lack of self-confidence during interactions. This study employs a quantitative approach using an experimental method (specifically, a pre-experimental one-group pre-test/post-test design) and utilizes SPSS version 23 for Windows for data analysis. The study population consisted of 25 students, with a sample of 10 students exhibiting high levels of speaking anxiety selected via purposive sampling. Hypothesis testing and data analysis revealed a mean pre-test score of 100.60 and a mean post-test score of 90.50, indicating a reduction in speaking anxiety of 10.10. Thus, it can be concluded that this intervention is effective in helping students reduce their speaking anxiety. These findings are expected to serve as a reference for school counselors in designing appropriate group counseling services to alleviate students' speaking anxiety.